Are heated tobacco products (HTPs) a public health opportunity? - Costanzo, Roberta; Baker, Gizelle (Medical Word, 2021)
Heated tobacco products (HTPs) are a new, rapidly emerging category of tobacco products that are designed to heat the tobacco instead of burning it, thus substantially reducing the emission of harmful chemicals. Currently there is a debate about whether HTPs provide an opportunity for public health, to accelerate the decline in cigarette smoking prevalence and thereby smoking-related population harm. To answer this question, HTPs have to be scientifically substantiated to reduce the harm to the individual smoker, but they also have to be satisfying for adult smokers to maximize the number of adult smokers who switch, while minimizing the number of youths and non-smokers who initiate or relapse to these products, as well as minimizing the number of smokers who intend to quit who may use those products instead. In this article we present the evidence showing that switching to the THS reduces the negative health effects that are triggered by chronic exposure to the toxic substances generated during tobacco combustion and that lead to disease, compared to continuing smoking.